Description of the Earliest Fossil Penguin from South America and First Paleogene Vertebrate Locality of Tierra Del Fuego, Argentina - Clarke, Julia (2003)
We report the discovery of the first vertebrate from the Paleogene of Tierra del Fuego (Isla Grande), Argentina, in southernmost South America. The specimen consists of parts of an associated pelvic girdle and limb that are identified as belonging to the penguin stem clade (Aves: Pansphenisciformes). The specimen, from an exposure of the Leticia Formation (late middle Eocene), is the earliest known penguin (pansphenisciform) from South America. It is more than 20 million years older than the earliest previously recorded South American penguins (from the late Oligocene–early Miocene) and, thus, almost doubles their known record on the continent. A detailed description of the new specimen and a discussion of its implications for the understanding of penguin morphological evolution are provided. The new specimen and other fossil penguins do not currently point to the origin of extant, or crown clade, penguin lineages (Spheniscidae), by the Eocene, only to the divergence of the penguin stem lineage from its sister taxon by this time. The new fossil has several morphologies that differ from all extant penguins but are shared with other fossil penguin taxa, suggesting they may be outside Spheniscidae. However, in a discussion of the current status of penguin systematics, we suggest the urgent need for comprehensive phylogenetic analysis of fossil and extant penguins to clarify the timing and pattern of penguin diversification. The specimen was recovered from a newly identified fossil vertebrate locality, an exposure of the Eocene Leticia Formation at Punta Torcida on the Atlantic shore of southeastern Tierra del Fuego, Argentina. The new locality is introduced, and a brief geologic description is made, highlighting the potential of the shallow marine sediments of the Leticia Formation for contributing to our knowledge of the Paleogene vertebrate fossil record of Tierra del Fuego, and of southern South America, generally